2006
DOI: 10.1177/105678790601500305
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Turkish Computer Teachers: Problems and Predictors

Abstract: Because computing has been considered to be one of the survival skills of the knowledge age (Trilling & Hood, 1999), many recent educational reform initiatives in developing countries include a computer literacy stage for students and teachers and, later, an information and communication technology diffusion stage to improve access to education, increase the quality of education, and implement educational reform (Arias & Clark, 2004; Perraton, 2000). In 1998, the Turkish Ministry of National Education (MNE) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
(33 reference statements)
1
4
0
11
Order By: Relevance
“…The differences between what pre-service teachers are supposed to do when they start working and what is expected from them were expressed by several lecturers. The findings like information technologies teachers are regarded as technical staff by the school administration and teachers and their job descriptions are not clear enough are similar to many other research findings (Çuhadar & Dursun, 2010;Demirli, Kerimgil & Donmuş, 2012;Deryakulu, 2006;Erdoğan, 2008;Eren & Uluuysal, 2012;Henkoğlu & Yıldırım, 2012;Karal & Timuçin, 2010;Kıyıcı & Kabakçı, 2006;Odabaşı vd, 2011;Seferoğlu & Akbıyık, 2009). It was deduced that the main reason for this was information technology teachers are considered as experts, technical service staff or officials who have the know-how about everything.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The differences between what pre-service teachers are supposed to do when they start working and what is expected from them were expressed by several lecturers. The findings like information technologies teachers are regarded as technical staff by the school administration and teachers and their job descriptions are not clear enough are similar to many other research findings (Çuhadar & Dursun, 2010;Demirli, Kerimgil & Donmuş, 2012;Deryakulu, 2006;Erdoğan, 2008;Eren & Uluuysal, 2012;Henkoğlu & Yıldırım, 2012;Karal & Timuçin, 2010;Kıyıcı & Kabakçı, 2006;Odabaşı vd, 2011;Seferoğlu & Akbıyık, 2009). It was deduced that the main reason for this was information technology teachers are considered as experts, technical service staff or officials who have the know-how about everything.…”
Section: Resultssupporting
confidence: 59%
“…Öğretmen adaylarının göreve başladıklarında yapmaları gerekenler ile kendilerinden beklenenler arasındaki farklılıklar, birçok öğretim elemanı tarafından ifade edilmiştir. Bilişim teknolojileri öğretmenlerinin, okul idaresi ve öğretmenler tarafından birer teknik eleman gibi görülmesi, görev tanımının net olmamasına ilişkin bulgular birçok araştırma sonuçlarıyla benzerlik göstermektedir (Çuhadar & Dursun, 2010;Demirli, Kerimgil, & Donmuş, 2012;Deryakulu, 2006;Erdoğan, 2008;Eren & Uluuysal, 2012;Henkoğlu & Yıldırım, 2012;Karal & Timuçin, 2010;Kıyıcı & Kabakçı, 2006;Odabaşı vd, 2011;Seferoğlu & Akbıyık, 2009). Bu durumun temel sebebi olarak; BT öğretmenlerinin teknolojiyle ilgili her konudan anlayan birer uzman, teknik servis elemanı ve memur gibi görülmeleri olduğu ortaya çıkmaktadır.…”
Section: Tartışma Ve Sonuçunclassified
“…Age: Sari (2005), Sünbül (2003) and Deryakulu (2007) demonstrated that age was positively related to, and a significant predictor of, personal success. Sari (2005) and Sünbül (2003) observed that age positively predicted desensitisation, while Karakuş (2013) determined that age was negatively related to burnout for both female and male participants, and it was a significant predictor of burnout for men, but not for women.…”
Section: Locus Of Controlmentioning
confidence: 98%
“…The work load in school was reported to increase emotional burnout and desensitisation (Deryakulu, 2007). Accordingly, teachers' expectations about their duties may increase teacher burnout.…”
Section: Workloadmentioning
confidence: 99%
“…"İlköğretim Okulları Bilişim Teknolojileri Öğretmenleri Anketi", araştırmacı tarafından ilgili literatürün taranması sonucu elde edilen bilgiler ışığında hazırlanmıştır (Deryakulu, 2005(Deryakulu, , 2006Deryakulu, Olkun, 2007Kabakçı, Kurt, Yıldırım, 2008;Seferoğlu, 2007). Ankette yer alan maddelerin bir kısmının, Timuçin, Öngöz ve Tatlı ( 2007) tarafından geliştirilen bir çalışmadan esinlenerek hazırlanmasına rağmen, maddelerin çoğunluğu araştırmacının bilişim teknolojileri öğretmeni olarak kendi deneyimlerinden yararlanılarak hazırlanmıştır.…”
Section: İlköğretim Okulları Bilişim Teknolojileri öğRetmenleri Anketiunclassified